Upacara Ngaben ditinjau dalam Perspektif Iman Kristen - Lewi, Ayub Pangga; Cahyadi, Tjiong Eric; Yulianto, Auw Tammy; Simon (Jurnal Salvation, 2023)
Abstract: Bali Island is a famous island in the world. Besides being famous for its beautiful tourist attractions, the island is also famous for a unique ceremony called ngaben or the burning of corpses as a path taken by the Hindu people to reach the heaven or in Hindu spiritual terms called Moksa. The implementation of ngaben ceremony goes through a long process and requires high cost. The purpose of this writing was to equip evangelists who would carry out missions to Hindus. With an understanding of heaven from a Hindu perspective, evangelists could design the right mission strategy. The research in this paper used a qualitative descriptive method to get a comprehensive exposure. The literature study approach was also used by using library sources, such as books, journals and articles. The results showed that there was a religious concept to get eternal salvation after death. This research aimed to help the mediator who wanted to carry out God's mission to realize the religious meaning contained in the ngaben ceremony. This research suggested that it was important for a servant of God as an agent of God's mission on earth to understand this fundamental concept. Abstrak: Pulau Bali merupakan pulau yang terkenal di seluruh dunia. Disamping terkenal akan obyek wisatanya yang indah, pulau ini juga terkenal dengan sebuah upacara yang unik yaitu upacara Ngaben atau pembakaran mayat sebagai jalan yang ditempuh umat Hindu untuk mendapatkan sorga atau di dalam istilah kerohanian Hindu disebut “Moksa”. Pelaksanaan upacara ngaben melalui proses yang panjang dan membutuhkan biaya yang sangat besar. Tujuan penulisan ini adalah membekali penginjil yang akan melaksanakan misi kepada umat Hindhu. Dengan pemahaman akan sorga dari perspektif Hindhu maka penginjil dapat merancang strategi misi yang tepat. Penelitian dalam tulisan ini menggunakan metode deskriptif kualitatif untuk mendapatkan pemaparan secara komprehensif. Pendekatan studi Pustaka juga digunakan dengan menggunakan sumber-sumber Pustaka dari buku, jurnal dan artikel. Hasil penelitian menunjukkan adanya konsep religius yang bermakna keselamatan kekal setelah kematian. Penelitian ini bermaksud membantu seorang pelaksana misi Allah agar memahami makna religius yang terkandung di dalam upacara ngaben. Penelitian ini menyarankan pentingnya seorang hamba Tuhan sebagai agen misi Allah di bumi memahami konsep fundamental ini.